Investigating English Language Students’ Difficulties in Research Article Writing - Zakila Mardatila Ersyad,; Yudi Cahyono, Bambang (PANYONARA: Journal of English Education, 2025)
This study investigates the difficulties faced by students in the English Language Education program when writing research articles, a mandatory requirement for degree completion. Using an explanatory sequential mixed- methods design, data were collected from questionnaires completed by 66 students and semi-structured interviews with four selected participants from universities in Malang, Indonesia. The study explored the types of writing difficulties experienced by EFL undergraduate students and identified the key factors contributing to these challenges. The findings reveal that language problems, particularly grammar, vocabulary, and sentence structure, are the most significant difficulties in research article writing. Content-related challenges, such as organizing ideas coherently and developing detailed arguments, also significantly affect students. Additionally, students struggle with understanding the structure of research articles and with citation and referencing conventions. Psychological and procedural factors, including limited supervisor feedback and poor time management, exacerbate these difficulties. These results provide valuable insights for educators to develop targeted strategies that address both technical and psychological barriers, thereby supporting students in improving their academic writing skills and succeeding in research article writing.